Reproductive Biodynamics of Short Mackerel (Rastreliger brachyoma Bleeker, 1851) in the Northern Waters Makassar Strait, Indonesia - Wayan Kantun; Ardi Eko Mulyawan; Hadijah Mahyuddin (Universitas Gadjah Mada, 2022)
Short mackerel are caught with high intensity by the fisherman and using various fishing gear. It is feared that this activity could change the reproduction habits of short mackerel in ther habitat. This study aims to analyze the bio-dynamics reproduction of short mackerel, including sex ratio, maturity stage, length at first maturity, length at first spawning, and fecundity. The survey method obtained the sample collection from the fish landing sites. Samples were collected in 1320 samples consisting of 651 females (13.0-16.5 cm) and 669 males (13.3-17.4 cm). The results showed that the sex ratio was balanced (1.00:1.02), the stage of gonad maturity showed from immature gonad to spawning (I to V), and the highest gonad maturity index for males and females were found in July (1.609 and 1.794). The length at first maturity of males and females had occurred when they were 16.51 cm and 16.63 cm, and the length at first spawning for males and females was 17.12 cm and 17.03 cm in size. The fecundity of female mackerel ranges from 30.106 to 58.439 in the northern waters of Makassar Strait. Capturing fish is suggested with a length above the spawned fish (>17 cm), considering that the fish only spawn at least once from their life cycle. The fecundity of short mackerel is relatively high as an indicator of high reproductive potential.